The Impact of Children’s Gender on Family Housing Assets - Tan, Minting (Transactions on Economics, Business and Management Research, 2024)
China’s household asset investment shows the characteristics of real estate concentration, which reduces the short-term risk-resistant ability of households and restricts the consumption ability of residents. This paper puts forward the theoretical hypothesis that “families whose eldest son is a boy have stronger housing investment motives”. A probit model is constructed using data from CHFS2019 for empirical testing. The results find that households whose eldest son is a boy have a stronger propensity to invest in housing than households whose eldest son is a girl. The degree of local sex ratio imbalance and the risk attitude of the head of household also influence investment behavior.